2011
DOI: 10.1016/j.cbpa.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Toward mechanistic classification of enzyme functions

Abstract: Classification of enzyme function should be quantitative, computationally accessible, and informed by sequences and structures to enable use of genomic information for functional inference and other applications. Large-scale studies have established that divergently evolved enzymes share conserved elements of structure and common mechanistic steps and that convergently evolved enzymes often converge to similar mechanisms too, suggesting that reaction mechanisms could be used to develop finer-grained functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…These proteins share 1) a (␤/␣) 7 ␤-barrel domain (a modified (␤/␣) 8 -barrel (TIM barrel)) containing the active site functional groups that support chemistry and 2) an ␣ϩ␤-capping domain formed from polypeptide segments at the N and C termini that provide many of the determinants for substrate recognition (6). Later, the structural similarity to enolase was recognized, 4 establishing the "enolase superfamily" (7). The substrates for MLE, MR, and enolase are carboxylate anions with a proton on the ␣-carbon.…”
Section: Sequence-structure-function Relationships In Enolase Superfamentioning
confidence: 99%
“…These proteins share 1) a (␤/␣) 7 ␤-barrel domain (a modified (␤/␣) 8 -barrel (TIM barrel)) containing the active site functional groups that support chemistry and 2) an ␣ϩ␤-capping domain formed from polypeptide segments at the N and C termini that provide many of the determinants for substrate recognition (6). Later, the structural similarity to enolase was recognized, 4 establishing the "enolase superfamily" (7). The substrates for MLE, MR, and enolase are carboxylate anions with a proton on the ␣-carbon.…”
Section: Sequence-structure-function Relationships In Enolase Superfamentioning
confidence: 99%
“…Assigning biochemical function is challenging in functionally diverse enzyme superfamilies. A recent survey by Babbitt and coworkers estimates that there are approximately 275 superfamilies encompassing two or more distinct biochemical functions, representing approximately one-third of the known enzyme universe (5). The functionally diverse enolase superfamily has provided a particularly challenging "model system" for developing methods for predicting and characterizing enzyme specificity (6).…”
mentioning
confidence: 99%
“…When predicted enzyme functions on our random control gene sets, TRACE could achieve a TOP precision of 36% and AUC value of 93.5%, in which TOP is defined as the proportion of highest-ranked positive control genes, and AUC defined as the value of area under a receiver operating characteristic curve (see Methods and Materials for further explanation). Enzymes were assigned with an EC number according to experimental characterization, rather than sequence similarity alone [27], [28]. Therefore, the high precision achieved by TRACE indicated that it can predict gene function not solely based on sequence similarity.…”
Section: Resultsmentioning
confidence: 99%